2010
DOI: 10.1038/nature08781
|View full text |Cite
|
Sign up to set email alerts
|

Variability in gene expression underlies incomplete penetrance

Abstract: The phenotypic differences between individual organisms can often be ascribed to underlying genetic and environmental variation. However, even genetically identical organisms in homogenous environments vary, suggesting that randomness in developmental processes such as gene expression may also generate diversity. In order to examine the consequences of gene expression variability in multicellular organisms, we studied intestinal specification in the roundworm Caenorhabditis elegans in which wild-type cell fate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
649
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 618 publications
(666 citation statements)
references
References 48 publications
12
649
1
4
Order By: Relevance
“…45 Eleven of the 14 CNVs that we identified were inherited from an unaffected parent and were considered to be of potential relevance to CP. Reasons for discordance between parent and child could include variable expressivity, 46 incomplete penetrance, 47 and epigenetic modification of gene expression. 47 Expression of a clinical phenotype in the child but not in the parent could also be explained by the 'two hit' hypothesis, 20,23 which postulates the additive effects of two or more de novo or inherited genetic abnormalities in the affected individual, with fewer such abnormalities in the unaffected parent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Eleven of the 14 CNVs that we identified were inherited from an unaffected parent and were considered to be of potential relevance to CP. Reasons for discordance between parent and child could include variable expressivity, 46 incomplete penetrance, 47 and epigenetic modification of gene expression. 47 Expression of a clinical phenotype in the child but not in the parent could also be explained by the 'two hit' hypothesis, 20,23 which postulates the additive effects of two or more de novo or inherited genetic abnormalities in the affected individual, with fewer such abnormalities in the unaffected parent.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for discordance between parent and child could include variable expressivity, 46 incomplete penetrance, 47 and epigenetic modification of gene expression. 47 Expression of a clinical phenotype in the child but not in the parent could also be explained by the 'two hit' hypothesis, 20,23 which postulates the additive effects of two or more de novo or inherited genetic abnormalities in the affected individual, with fewer such abnormalities in the unaffected parent. Other mechanisms include the presence of a point mutation on the other allele in the affected children, not identified by the CNV profiling, 48 and various combinations of CNVs and point mutations affecting different genes.…”
Section: Discussionmentioning
confidence: 99%
“…This study also presents a biomathematical approach that could provide a conceptual framework to analyze a recurrent and controversial point in developmental biology: the problem about ''determinism'' and ''stochasticity'' and their possible role in developing organisms (Bronk et al, 1968;Saunders et al, 2002;Meng et al, 2004;Song et al, 2006;Raj et al, 2010;Zernicka-Goetz and Huang, 2010;Wu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we showed that certain parameter combinations are responsible for bursty temporal patterns. While there is strong experimental evidence supporting transcriptional bursts both in prokaryotes (Golding et al, 2005) and (especially) in eukaryotes (Raj et al, 2006), the underlying biological mechanism still remains unclear. Even though many complex mechanisms, involving the biochemical machinery of DNA transcription, seem to contribute to pulsatile transcription (as suggested in Golding et al (2005)), our study supports the fact that gene regulation mechanisms themselves (and the relative speed of the different reactions involved) play an important role in determining this pattern of transcription.…”
Section: Analysis Of Stochastic Behaviourmentioning
confidence: 99%
“…Thus, it is becoming clear that noise and stochasticity underlie critical events in cell's life such as differentiation and decision making (Balázsi et al, 2011). Moreover, some authors suggest that random phenotypic switching can represent an efficient mechanism for adapting to fluctuating environments (see, e.g., Balázsi et al, 2011;Raj et al, 2010). These findings have raised new interest in analysing the role of noise in gene expression.…”
Section: Introductionmentioning
confidence: 99%